The Politics of Lineage: Caste, Kinship and Land Control in an Agrarian Frontier - Girija Joshi (South Asia Multidisciplinary Academic Journal)
This paper traces the shifting loci of community in rural Haryana (“the Delhi frontier”) in the early nineteenth century, focusing particularly upon caste and kinship. It suggests that categories later identified by bureaucrats and scholars as “caste” and “tribe” in this region were in fact simply broad ethnic labels that represented only very abstract communities. It will further demonstrate that in this mobile agrarian frontier, kinship categories (such as the clan) had historically crystallized around the control of land. By implication, kinship was a vehicle of resource consolidation, whose boundaries were determined at least in part by this pragmatic consideration. An appreciation of the political dimension of kinship brings complexity to our understanding of rural politics, highlighting that the “village community” was far from being a historically stable polity.